Improving the performance of an anionic MOF by counter cation replacement as electrode material in a full cell setup of a potassium ion capacitor. Issue 18 (19th April 2023) - Aphirakaramwong, Chalita; Akintola, Oluseun; Plass, Christian T.; Sawangphruk, Montree; Plass, Winfried; Balducci, Andrea
Abstract : Potassium-based energy storage devices are attracting increasing attention as an alternative to lithium and sodium systems. Abstract : Potassium-based energy storage devices are attracting increasing attention as an alternative to lithium and sodium systems. In addition, metal–organic frameworks (MOFs) can be considered as promising electrode materials for this type of device due to their advantageous properties. Herein, the anionic MOF JUMP-1 and its analog with pre-loading of potassium cations, namely JUMP-1(K), were synthesized and characterized. The anionic framework of JUMP-1 is found to be extremely stable towards the exchange of the dimethylammonium cations by potassium ions. These MOFs were tested in composite electrodes in combination with conventional organic electrolytes as anode materials in a potassium-based system, including the full cell assembly of a potassium ion capacitor (KIC). The results show the significant improvement in capacity between the pristine JUMP-1 and the potassium-exchanged analog JUMP-1(K) as electrode materials. KICs containing JUMP-1(K) coupled with activated carbon (AC) display a promising stability over 4000 cycles. According to the results from these studies, the composite MOF electrode with the potassium-exchange analog JUMP-1(K) presents a promising approach, for which the electrochemical performance compared to the pristine anionic MOF is significantly enhanced.